Abstain, be faithful and condomise : how high school learners understand and prioritise HIV/AIDS message of combating HIV infection - snkosi@tuks.co.za (University of Pretoria, 2013)
Dissertation (MEd (Educational Leadership & Management))--University of Pretoria, 2009.